High-Concentration Synthesis of Sub-10-nm Copper Nanoparticles for Application to Conductive Nanoinks - Hokita, Yuki; Kanzaki, Mai; Sugiyama, Tomonori; Arakawa, Ryuichi; Kawasaki, Hideya (ACS applied materials & interfaces, 2015)
A simple, high-concentration (up to 0.6 M Cu salt) synthesis of sub-10-nm copper nanoparticles (Cu NPs) was developed in ethylene glycol at room temperature under ambient air conditions using 1-amino-2-propanol (AmIP) as the stabilizer. Monodispersed AmIP-Cu NPs of 3.5 ± 1.0 nm were synthesized in a high yield of ∼90%. Thus, nearly 1 g of sub-10-nm Cu NP powder was obtained using a one-step synthesis for the first time. It is proposed that metallacyclic coordination stability of a five-membered ring type between the Cu and AmIP causes the high binding force of Am IP onto the Cu surface, resulting in the superior stability of the AmIP-Cu NPs in a solution. The purified powder of AmIP-Cu NPs can be redispersed in alcohol-based solvents up to high Cu contents of 45 wt % for the preparation of Cu nanoink. The resistivity of the conductive Cu film obtained from the Cu nanoink was 30 μΩ cm after thermal heating at 150 °C for 15 min under a nitrogen flow. The long-term resistance stability of the Cu film under an air atmosphere was also demonstrated.